Analisi Terhadap Penyehatan Perusahaan Melalui PKPU yang Berkeadilan - Tami Rusli (Universitas Bandar Lampung (UBL), 2016)
Settlement of debts which could lead to bankruptcy debtor, in order to avoid gaps in implementation, bankruptcy was supposed to be an institution that is final, that is to say before the bankruptcy of the debtor